Electroconvulsive therapy knowledge and attitudes among patients and caregivers in South China: A preliminary study - Deng, Can-Jin; Nie, Sha; Mai, Jian-Xin; Huang, Xiong; Huang, Xing-Bing; Zheng, Wei (Frontiers in Psychiatry, 2023)
Abstract Background: Electroconvulsive therapy (ECT) is a safe and effective therapy for individuals suffering from major psychiatric disorders, but attitudes towards ECT among patients and caregivers have not been well studied. This study was conducted to elucidate patient and caregiver knowledge and attitudes concerning ECT in South China. Methods: The sample comprised 92 patients diagnosed with major psychiatric disorders and their caregivers (n=92). Participants completed questionnaire measures of knowledge and attitudes related to ECT. Results: Information before ECT was inadequately provided to both caregivers and patients (55.4% versus 37.0%, P<0.05). Caregivers reported receiving more adequate information about the therapeutic effects (50.0% versus 44.6%), side effects (67.4% versus 41.3%), and risks (55.4% versus 20.7%) of ECT when compared to patients (all P<0.05). However, less than half of patients and caregivers believed that ECT was effective (43.5% versus 46.7%, P>0.05), while more than half of them believed that ECT was beneficial (53.3% versus 71.7%, P<0.05), and approximately half of them believed that ECT was safe (50.0% versus 51.1%, P>0.05). A total of 32.6% of patients and 55.4% of caregivers (P<0.05) reported that ECT was used only for critically ill patients. A total of 62.0% of patients experienced side effects, with memory impairment being the most commonly reported. Conclusions: Clinicians should develop a systematic health education program before ECT treatment and ensure that patients and caregivers have an accurate understanding of ECT, particularly the treatment process, its therapeutic effects and potential side effects prior to administering this treatment. Keywords: electroconvulsive therapy; major psychiatric disorders, caregivers; attitudes; knowledge.